Computer simulation and SERR detection of cytochrome c dynamics at SAM-coated electrodes - Álvarez Paggi, Damián Jorge (2009)
In this paper we present a combined experimental and theoretical study of the heterogeneous electron transfer reaction of cytochrome c electrostatically adsorbed on metal electrodes coated with monolayers of 6-mercaptohexanoic acid. Molecular dynamics simulations and pathways calculations show that adsorption of the protein leads to a broad distribution of orientations and, thus, to a correspondingly broad distribution of electron transfer rate constants due to the orientation-dependence of the electronic coupling parameter. The adsorbed protein exhibits significant mobility and, therefore, the measured reaction rate is predicted to be a convolution of protein dynamics and tunnelling probabilities for each orientation. This prediction is confirmed by time-resolved surface enhanced resonance Raman which allows for the direct monitoring of protein (re-)orientation and electron transfer of the immobilised cytochrome c. The results provide a consistent explanation for the non-exponential distance-independence of electron transfer rates usually observed for proteins immobilized on electrodes. © 2009 Elsevier Ltd. All rights reserved.